Testing a New Mediational Model of the Link Between Maltreatment and Aggression in Adolescence in Upstate New York, 2002-2004 - Bradshaw, Catherine P. ([Verlag nicht ermittelbar], 2009)
This study sought to examine whether adolescents who experience rejection by both peers and parents would demonstrate higher levels of aggression due to negative views of the self and/or others. In Part 1 (Older Adolescent Data), participants were 125 male and female undergraduate students ranging in age from 18 to 27 years, who were recruited from psychology and human development classes in upstate New York between 2002 and 2003 and received course credit for participating in a study of relationships and problem solving. In small group testing sessions, participants completed assessments of several personality factors, justification of aggression, self-esteem, other-esteem, and aggression. Participants also completed the hypothetical situations task in which they assessed the provocateur's intent and their own likely response in each. For Part 2 (Adolescent Data), participants included 184 adolescents who were between the ages of 14 and 17 and enrolled at a suburban high school in upstate New York in 2003 and 2004. Adolescents were recruited to participate in a study of relationships and problem solving through announcements made by the researcher in the students' homeroom. A total of nine homerooms participated across two academic years. Each participating student's homeroom teacher completed an assessment regarding the student's behavior. As in Part 1, the students completed several self-assessments and a hypothetical situations tasks. Both Parts 1 and 2 include the demographic variables age, race, and gender and scores from the personality factors, justification of aggression, self-esteem, other-esteem, and aggression assessments and the hypothetical situations task. Part 2 also includes variables from the homeroom teacher's assessment of the student's behavior.